1999
DOI: 10.1375/136905299320565942
|View full text |Cite
|
Sign up to set email alerts
|

Self–transcendence as a measure of spirituality in a sample of older Australian twins

Abstract: Measures of self-transcendence, physical health and psychological well-being were included in a self-report Health and Lifestyle questionnaire administered to Australian twins aged over 50 between 1993 and 1995. Self-transcendence appears to be higher among older Australian women than men, and was significantly associated with religious affiliation, marital status (in women) and age (in men). No strong correlations were observed between self-transcendence and any measure of psychological or physical health. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Conversely, in a solely Australian study, Kirk et al (1999a) show no effect of genetic factors and find that shared environmental factors have the largest effect in adulthood, accounting for about 60% of the variance in church attendance in twins over 50 years of age. Kirk et al (1999a) also study self-transcendence in this sample of older Australian twins and show that genetic factors contribute approximately 40%, while unique environmental factors contribute 50%, and shared environmental factors contribute 10% of the variance. Bouchard et al (1999) employ a construct of intrinsic and extrinsic religiousness in an American study and demonstrate significant heritability for both measures.…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…Conversely, in a solely Australian study, Kirk et al (1999a) show no effect of genetic factors and find that shared environmental factors have the largest effect in adulthood, accounting for about 60% of the variance in church attendance in twins over 50 years of age. Kirk et al (1999a) also study self-transcendence in this sample of older Australian twins and show that genetic factors contribute approximately 40%, while unique environmental factors contribute 50%, and shared environmental factors contribute 10% of the variance. Bouchard et al (1999) employ a construct of intrinsic and extrinsic religiousness in an American study and demonstrate significant heritability for both measures.…”
mentioning
confidence: 72%
“…In other words, to some degree we are as we are in our behavior and personality because we have inherited genes that make us that way. Over the past decade, an increasing number of studies have explored the genetic and environmental influences on a rather new and perhaps provocative realm: religiousness, often using the twin study design to facilitate assessment of the impact of genetic, shared environmental and unique environmental factors (Kendler et al, 1997;Kendler & Myers, 2009;Kirk et al, 1999aKirk et al, , 1999bKoenig et al, 2005Koenig et al, , 2008Tsuang et al, 2002;Vance et al, 2010). The twin study design takes advantage of the fact that twins are reared in the same environment, but while monozygotic (MZ) twins share all of their genes, dizygotic (DZ) twins share on average half of their genes and hence differences in intrapair similarity between the two may indicate the presence of a positive heritability.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This is in contrast to the heritable dimensions of temperament for which familial aggregation is best explained by additive genetic effects alone Stallings et al, 1996). Previously, Kirk et al found that additive genetic effects accounted for 48% of the variance in Self-transcendence scores for men and women alike (Kirk, Eaves, & Martin, 1999). In addition to demonstrating trait heritability, it is desirable to determine whether a trait provides additional information beyond that which can be already explained by existing personality taxonomies.…”
Section: Objectivementioning
confidence: 99%